Guided assembly, nanostructuring and functionalization with brushes of microscale polymer cubes for tailored 3-D cell microenvironments. (April 2019) - Steuber, Marc; Schönherr, Holger
Graphical abstract: Highlights: Polymer-based strategy of guided assembly of building blocks affords cell microcompartments. Building blocks possess topographic nanostructures and (bio)interfacial functionality viatailored polymer brush coatings. Unique individualized and tailored microcompartments were realized, compatible with real-time study of individual cells. Abstract: The knowledge of fundamental aspects in cell biology has rapidly increased in the last decades also aided by the fabrication of artificial cell microenvironments in both 2-D and 3-D. To overcome the current lack of spatial control of parameters affecting cellular fate in structure-property relationship studies, including topographic nanostructures and biointerfacial cues, a new strategy comprising the fabrication of microscale polystyrene building blocks, their nanostructuring and functionalization with polymer brushes as well as their guided assembly into single cell microcompartments is introduced. By micromanipulation of individual building blocks, which may possess different topographic nanopatterns and biochemical functionality, individualized and tailored microcompartments were realized that were shown to be compatible with the real-time study of individual cells and their behavior in those microenvironments.